Behavioral Contracts to Minimize Smartphone Rescue for Student Study Time at Home - Muslih, Yuyun Nuriyah (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
The research objective is to learn how to use contracts to minimize the success of smartphones while studying students at home. The study was conducted on 5 students of SMAN 3 Kota Tasikmalaya who were selected using proportional random sampling technique in one group pretest-posttest design experiment. Meanwhile, to analyze data using descriptive and nonparametric statistics. The results of the preliminary study showed that smartphones when studying students showed a category of users at risk. However, after the training is given it becomes a regular user category (increased), so students can take advantage of learning time easily and manage more readiness in overcoming learning in school. The trial results show significant results obtained by Asymp values. Sig = 0.038 <of a (0.05) then rejected means that there are differences in students using smartphone compilation learning at home before and followed by counseling using motivational contract techniques, using contract techniques proven effective to minimize smartphones based on student learning time at home. This shows the technique of a contract that can be agreed as one that asks for help and counseling in minimizing smartphones while studying.